Conférence: «Travail et santé au travail des femmes en contexte de pandémie» (2020)
La pandémie de COVID-19 a mis en lumière combien les femmes étaient en première ligne dans le système hospitalier et dans les soins aux personnes âgées au Québec. En d’autres mots : la pandémie a révélé l’importance de nombreux métiers mal rémunérés et souvent négligés, dont on se soucie peu, qui sont occupés à 80% par des femmes.
Keywords: 2000 à aujourd'hui; amériques; covid-19; femmes*; pandémie; personnes âgées; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques; travail; travail des femmes*

LET'S GET YOU PREGNANT! : exploration critique de l'échec de la fécondation in vitro dans une pratique de l'installation - Barkun, Heidi (Université du Québec à Montréal, 2020)
Ce travail de recherche-création explore l’expérience de l’échec de la fécondation in vitro en employant une méthodologie d’autobiographie ancrée dans une critique institutionnelle féministe. Ayant suivi quatre ans de traitements de fertilité infructueux, j’incorpore ce vécu dans ma pratique émergente de l’installation contextuelle. Dans le chapitre I, je défends ma position en tant que sujet et objet de cet ouvrage. Le chapitre se termine avec une liste de termes employés dans ce mémoire. Le chapitre II considère les systèmes sociaux, médicaux et politiques qui gardent la maternité au premier plan de vie des femmes ; la fécondation in vitro y est examinée dans ce contexte élargi. La collection comme moyen de production artistique est analysée en lien avec l’œuvre Artéfacts provenant d’un rituel contemporain de fertilité (2016). Le chapitre III étudie la notion de l’échec et son impact sur les femmes en traitement de fertilité qui n’arrivent pas à devenir mères. Les pressions sociales et médicales qui amènent les femmes à utiliser la fécondation in vitro sont abordées en lien avec l’installation socially acceptable childlessness (2017) ; et la déhiérarchisation du site de l’œuvre est examinée en lien avec Échec quantifié (2017). Le chapitre IV analyse les politiques de l’espace et du son. Mon projet final LET’S GET YOU PREGNANT! explore le pouvoir de la parole en présentant le récit de 28 participantes, moi incluse, qui ont utilisé la fécondation in vitro sans succès et qui n’étaient pas mères au moment de l’entretien. L’élévation de la collection d’artéfacts de 16 des 28 participantes en statut d’œuvre d’art est étudiée. La possibilité de mener un éveil social par la voie de l’art conclut ce mémoire qui interroge l’industrie de la fécondation in vitro et repense la poursuite du succès à tout prix. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Installation – Fécondation in vitro – Échec – Corps féminin – Infertilité
Keywords: 2000 à aujourd'hui; IREF; arts visuels et médiatiques; discipline; mémoires/thèses; périodes historiques; recherche-création; ressource en ligne; santé; santé reproductive; thématiques

Femmes et Environnement. Enjeux d'égalité pour toutes les femmes - Boivin, Martine (Le Réseau des Tables régionales de groupes de femmes du Québec, 2020)
Le Réseau des Tables régionales de groupes de femmes du Québec est un regroupement provincial composé des 17 Tables régionales de groupes de femmes au Québec. Il s’agit d’un regroupement féministe de défense collective des droits, qui travaille sur les questions mettant en jeu les intérêts et les droits des femmes. La spécificité du regroupement est représentée par l’expertise régionale développée par les Tables régionales dans les dossiers de la condition féminine. Porte-voix des régions auprès des instances nationales, le RTRGFQ favorise la prise de parole collective des Tables régionales, tout en respectant leurs particularités. Le RTRGFQ et les Tables régionales sont en action depuis plus de 20 ans pour favoriser la participation des femmes à la vie démocratique québécoise
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; charge mentale; charge émotionnelle; environnement; intersectionnalité; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques

Coronavirus, domestic labour and care: Gendered roles locked down - Craig, Lyn (Journal of Sociology, 2020)
The Covid-19 pandemic turned daily lives upside down. Lockdowns and physical distancing meant hundreds of thousands of people switched to working from home, significantly blurring the temporal and spatial boundaries between paid work, domestic labour and caring for others. This article explores gender relations, and the division of employment, domestic labour and care, drawing on early results from an online survey, Work and Care in the Time of Covid-19, carried out between 7 May and 4 June 2020.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; australie; care; covid-19; discipline; division sexuelle du travail; océanie; pandémie; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail de reproduction; travail invisible

Menstrual health and period poverty among young people who menstruate in the Barcelona metropolitan area (Spain): protocol of a mixed-methods study - Medina-Perucha, Laura; Jacques-Aviñó, Constanza; Valls-Llobet, Carme; Turbau-Valls, Rosa; Pinzón, Diana; Hernández, Lola; Canseco, Paula Briales; López-Jiménez, Tomàs; Lizarza, Enara Solana; Feliu, Jordina Munrós; Berenguera, Anna (BMJ Open, 2020)
Introduction The importance of menstrual health has been historically neglected, mostly due to taboos and misconceptions around menstruation and androcentrism within health knowledge and health systems around the world. There has also been a lack of attention on ‘period poverty’, which refers to the financial, social, cultural and political barriers to access menstrual products and education. The main aim of this research is to explore menstrual health and experiences of period poverty among young people who menstruate (YPM). Methods and analysis This is a convergent mixed-methods study, which will combine a quantitative transversal study to identify the prevalence of period poverty among YPM (11–16 years old), and a qualitative study that will focus on exploring menstruation-related experiences of YPM and other groups (young people who do not menstruate (YNM); primary healthcare professionals; educators and policy-makers). The study will be conducted in the Barcelona metropolitan area between 2020 and 2021. Eighteen schools and 871 YPM will be recruited for the quantitative study. Sixty-five YPM will participate in the qualitative study. Forty-five YNM and 12 professionals will also be recruited to take part in the qualitative study. Socioeconomic and cultural diversity will be main vectors for recruitment, to ensure the findings are representative to the social and cultural context. Descriptive statistics will be performed for each variable to identify asymmetric distributions and differences among groups will be evaluated. Thematic analysis will be used for qualitative data analyses Ethics and dissemination Several ethical issues have been considered, especially as this study includes the participation of underage participants. The study has received ethical approval by the IDIAPJGol Research Ethics Committee (19/178 P). Research findings will be disseminated to key audiences, such as YPM, YNM, parents/legal tutors, health professionals, educators, youth (and other relevant) organisations, general community members, stakeholders and policy-makers, and academia.
Keywords: 2000 à aujourd'hui; 2020-2029; adolescentes*; discipline; espagne; europe; médecine; projet charge mentale; périodes historiques; régions géographiques; santé; santé menstruelle; santé publique; thématiques

Comment la crise fait-elle ressortir les inégalités de genre ? - Plumauzille, Clyde (2020)
Aides-soignantes, caissières, aides à domicile… ce sont majoritairement des femmes qui se retrouvent en première ligne contre le virus. Comme le rappelle l’historienne Clyde Plumauzille dans ce podcast, ces inégalités ne sont pas nouvelles, la prise en charge d’autrui au sein du foyer ou dans la société étant historiquement dévolue aux femmes.
Performers: _:n2788
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; charge mentale; confinement; covid-19; histoire et politique; hétérosexisme; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; violences; violences conjugales

Its about time we care about an equitable world: Women's unpaid care work and COVID-19 - Sarrasanti Ardinugroho, Nediana; Donkor, Felix Kwabena; Santos, Claudia; Tsagkari, Marula; Wannous, Chadia (IEEE Engineering Management Review, 2020)
Unpaid care work, mostly performed by women, is a central but undervalued contributor to economies. During the COVID-19 pandemic, the need for unpaid care work increased due to restricted movement, social isolation, and economic challenges. This pandemic has highlighted the urgency of recognizing and valuing women's work at the household level which has been systematically overlooked. At the same time, it has increased the demand for technology usage, exposing the gender digital divide. This article aims to shed light on the additional burden women are facing, especially when trying to balance unpaid care work with paid employment from the seclusion of their homes. We do this by reviewing a number of surveys conducted in Indonesia. We combine this with other examples from additional contexts in order to draw attention to a global trend of amplified inequalities and struggles women are experiencing. We advocate for an urgent paradigm shift by providing vital recommendations for policymakers and managers.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; covid-19; indonésie; pandémie; pauvreté; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail non rémunéré; travail précaire; violences; violences domestiques; violences envers les femmes*

The Impact of COVID-19 on women - United Nations (United Nations Entity for Gender Equality and the Empowerment of Women (UN Women); United Nations Secretariat, 2020)
The year 2020, marking the twenty-fifth anniversary of the Beijing Platform for Action, was intended to be ground-breaking for gender equality. Instead, with the spread of the COVID-19 pandemic, even the limited gains made in the past decades are at risk of being rolled back. The pandemic is deepening pre-existing inequalities, exposing vulnerabilities in social, political and economic systems which are in turn amplifying the impacts of the pandemic. Across every sphere, from health to the economy, security to social protection, the impacts of COVID-19 are exacerbated for women and girls simply by virtue of their sex. This policy brief by the UN Secretary-General explores how women and girls’ lives are changing in the face of COVID-19, and outlines suggested priority measures to accompany both the immediate response and longer-term recovery efforts.
Keywords: 2000 à aujourd'hui; 2020-2029; covid-19; discipline; droit; droits des femmes*; droits humains; pandémie; projet charge mentale; périodes historiques; santé; science politique et droit; thématiques; violences; violences sexistes et sexuelles

Adaptability to social distancing due to COVID-19 and its moderating effect on stress by gender - Zamarripa, Jorge; Delgado-Herrada, Maritza; Morquecho-Sánchez, Raquel; Baños, Raúl; de la Cruz-Ortega, Manuel; Duarte-Félix, Héctor (Salud mental, 2020)
The COVID-19 pandemic, originated in China, has affected millions of people worldwide, leading to various situations such as psychological disorders and diseases that affect people’s physical and mental health, and disrupt their quality of life. Objective. To analyze stress levels during social distancing due to COVID-19 by gender and to determine the moderating effect of adaptability to the situation. Method. The study is cross-sectional and quantitative, with a descriptive-correlational scope. The sample consisted of 1,173 Mexican subjects (522 males [44.5%] and 651 females [22.5%]) with an average age of 25.99 years (DT = 11.19; range = 12 - 77 years). Adaptability and perceived stress were measured, obtaining reliability from appropriate instruments. Results. The results indicated that the greater the number of weeks of social distancing, the higher the perceived level of stress. Also, the better people adapt to social distancing, the less stress occurs. Women were observed to have higher levels of stress compared to men. Discussion and conclusion. The findings highlight the importance of adaptability to the stressful situation of the pandemic, because the effect of severe stress on women largely disappears when there is a high level of adaptability to the event.
Number: 6 https://www.scielo.org.mx/scielo.php?script=sci_arttext&pid=S0185-33252020000600273
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; covid-19; mexique; périodes historiques; ressource en ligne; régions géographiques; santé; santé mentale; stress; thématiques; étude quantitative